Neurobiologically inspired mobile robot navigation and planning - Cuperlier, Nicolas; Quoy, Mathias; Gaussier, Philippe (Frontiers in Neurorobotics, 2007)
After a short review of biologically inspired navigation architectures, mainly relying on modeling the hippocampal anatomy, or at least some of its functions, we present a navigation and planning model for mobile robots. This architecture is based on a model of the hippocampal and prefrontal interactions. In particular, the system relies on the definition of a new cell type “transition cells” that encompasses traditional “place cells”.